TATHWÎR KITÂB AL-QIRÂAH AL-IDHÂFÎ ‘ALÂ ASÂS AL-QIYAM AL-AKHLÂQIYYAH LI TARQIYAH MAHÂRAH AL-QIRÂAH LADÂ TALÂMÎDZ AL-MADRASAH AL-MUTAWASSITHAH - Mustofa, Syaiful; Lutfiyatun, Eka; Muzakki, Akhmad (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
The research purpose is to develop Arabic reading books based on character values to improve the reading ability to find feasibility and effectiveness. This research is based on the ADDIE model (analysis, design, development, implementation, evaluation). The population is taken from the students in MTs.N 2 Tegal, it is class VIII-A (control group) class VIII-B (experimental group) by comparing pre-test and post-test scores. The data was collected by observation, interview, questionaires, document. The data analysis was done by using T. Test. The results showed it contained the inspirational short stories in each chapter. The theme was chararcter education values (religious, humanity, nationality), vocabulary tables. The design was 88%, the content was 87%, the character development rate was 90%. It is effective and has a significant effect on the development of student competencies, this is evidenced by an increase in student competence reaching 50% after field practice in the experimental group.